2021
DOI: 10.22541/au.163253284.44570038/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute Paediatric Mastoiditis in the UK Before and During the COVID-19 Pandemic: A National Observational Study

Abstract: Objectives To explore the impact of COVID-19 on the management and outcomes of acute paediatric mastoiditis across the UK. Design National retrospective and prospective audit Setting 48 UK secondary care ENT departments Participants Consecutive children aged 18 years or under, referred to ENT with a clinical diagnosis of mastoiditis. Main outcome measures Cases were divided into: Period 1 (01/11/19-15/03/20) before the UK population were instructed to reduce social contact, and Period 2 (16/03/20-30/04/21), fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…A reduction in pediatric acute mastoiditis cases has also been reported by several authors (28,29). In contrast, a Spanish study showed that, although there was no increase in ear, nose, and throat infections from January to April 2020 (a period encompassing also months before COVID in Spain) when compared with the same period in 2010 to 2019, there was a significant increase in complicated mastoiditis cases (e.g., subperiosteal abscess, facial nerve paralysis, intracranial abscess) (15).…”
Section: Discussionsupporting
confidence: 68%
“…A reduction in pediatric acute mastoiditis cases has also been reported by several authors (28,29). In contrast, a Spanish study showed that, although there was no increase in ear, nose, and throat infections from January to April 2020 (a period encompassing also months before COVID in Spain) when compared with the same period in 2010 to 2019, there was a significant increase in complicated mastoiditis cases (e.g., subperiosteal abscess, facial nerve paralysis, intracranial abscess) (15).…”
Section: Discussionsupporting
confidence: 68%
“…Over the last several decades, the incidence rate of mastoiditis, which closely related to hearing problems, as a complication of NPC has not signi cantly decreased, and our study showed that this incidence rate was still 35.6% [4,7]. NPC patients with mastoiditis often have tinnitus, hearing loss, swelling, pain, and other symptoms, which greatly impacts the quality of life in those patients [26,32,33]. Therefore, a therapeutic approach to prevent/treat NPC-caused mastoiditis is urgently needed.…”
Section: Discussionmentioning
confidence: 94%
“…There was not an equivalent rise in acute mastoiditis during the winter peak of AOM in January 2020. In addition, a national UK observation study of acute paediatric mastoiditis during COVID‐19 showed only one positive patient (0.9%) 13 . This suggests a low risk of otological complications from AOM in COVID‐19 patients.…”
Section: Discussionmentioning
confidence: 96%